The new economy: myth and reality. (Monthly Review: An Independent Socialist Magazine, 2001)
A special issue on the new economy is presented. Topics discussed include the myth and reality of the new economy; the same irrational economy; the new economy and the labor movement; the disposable worker; and the magical-market world of Disney. An interview with Doug Henwood is provided.